Nursing behaviour as a predictor of alternate-year reproduction in muskoxen - Schulman, Andrea B.; White, Robert G. (Rangifer, 1997)
Our finding significant differences in nursing behavior during the post-rut period supports the hypothesis that female muskoxen use factors other than their nutritional condition to determine their reproductive strategy.